Differences Between Self-Reported Psychotic Experiences, Clinically Relevant Psychotic Experiences, and Attenuated Psychotic Symptoms in the General Population - Moriyama, Tais Silveira; van Os, Jim; Gadelha, Ary; Pan, Pedro Mario; Salum, Giovanni Abrahão; Manfro, Gisele Gus; Mari, Jair de Jesus; Miguel, Eurípedes Constantino; Rohde, Luis Augusto; Polanczyk, Guilherme Vanoni; McGuire, Philip; Bressan, Rodrigo Affonseca; et al. (Frontiers in Psychiatry, 2019)
Purpose: Psychotic experiences in childhood (such as hearing voices or being suspicious) represent an important phenotype for early intervention. However, these can be defined in several ways: self-reported psychotic experiences that have not been validated by a clinician, or ‘false positive psychotic experiences’ (FPE), clinically validated psychotic experiences (CPE), and attenuated psychotic symptoms (APS). Very few studies have investigated how these distinctions impact on clinical and other domains. The present study aims to compare FPE, CPE and APS among children and adolescents. Methods: 2,241 individuals aged 6-14 years provided self-ratings of 20 psychotic experiences. A trained psychologist conducted an interview with the CAARMS to validate or reject reported experiences and to rate the presence of APS and affective flattening. In parallel, parents provided information about their children's mental health to an independent interviewer. We tested the association of mutually exclusive FPE, CPE and APS (FPE=33%; CPE=11%, APS=6%), with potential predictors (positive attributes, levels of psychopathology and blunted affect). Results: Most associations were qualitatively similar and there was a dose-response in the strength of associations across categories, such that APS> CPE> FPE. Experiences in all 3 categories were associated with female sex. FPE were associated with overall levels of psychopathology, but to a lesser degree than CPE and APS. APS and CPE were associated with less positive attributes, with APS more so than CPE. Only APS was associated with affective flattening. Conclusions: In children and adolescents, FPE, CPE and APS all index liability for psychopathology, but as clinical relevance increases, there are stronger associations with more specific measures of psychotic psychopathology.